CD133, but Not CD44, May Serve as a Novel Biomarker for Differential Diagnosis Between Basal Cell Carcinoma and Trichoblastomas - Bi Y; Shi X; Chen D; Zhao Y (Dove Medical Press, 2022)
Yalan Bi,1 Xiaohua Shi,2 Dian Chen,1 Yi Zhao1 1Department of Dermatology, Beijing Tsinghua Changgung Hospital, School of Clinical Medicine, Tsinghua University, Beijing, People's Republic of China; 2Department of Pathology, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People's Republic of ChinaCorrespondence: Yi Zhao, Department of Dermatology, Beijing Tsinghua Changgung Hospital, School of Clinical Medicine, Tsinghua University, No. 168 Litang Road, Changping District, Beijing, People's Republic of China, Tel/Fax +86 010 56119127, Email zhaoyimd@tsinghua.edu.cnPurpose: To investigate the clinical value of CD133 and CD44 as putative cancer stem cell markers in distinguishing between basal cell carcinoma (BCC) and trichoblastomas (TB).Patients and Methods: Tumor samples from 24 BCC and 23 TB patients were retrospectively retrieved for immunohistochemical staining of CD133 and CD44. The results were interpreted using a semiquantitative scoring system (H score). A receiver operating characteristic (ROC) curve was developed to identify an optimal cutoff value for differentiating between BCC and TB.Results: Expression of CD133 was significantly higher in BCC patients than in TB patients (median H score: 30 [IQR: 12.5- 56.3] vs 0 [IQR: 0- 2], P < 0.001). However, there was no significant difference in CD44 expression between the two groups (median H score: 105 [IQR: 63.8- 155.0] vs 60 [IQR: 30- 120], P = 0.095). The ROC analysis of CD133 immunostaining yielded an area under the curve (AUC) of 0.881 (95% CI: 0.756- 1.000) for differentiating between BCC and TB by using a H score of 7 as the cut-off value (98.5% sensitivity and 87.0% specificity). By contrast, immunostaining of CD44 showed a lower diagnostic value, with an AUC of 0.642 (95% CI: 0.476- 0.808) at the optimal cut-off value of 85 (62.5% sensitivity and 73.9% specificity). The positive and negative predictive values were 88.5% and 95.2% for CD133 and 71.4% and 65.4% for CD44, respectively. Additionally, CD133 expression was significantly associated with mitotic activity in BCC patients (r = 0.549, P = 0.005).Conclusion: Our study expanded upon previous studies of CD133 and CD44 expressions in skin tumors, suggesting that CD133, but not CD44, may serve as a novel biomarker for differential diagnosis of BCC, although future studies using a larger number of patients are needed to justify it further.Keywords: basal cell carcinoma, BCC, trichoblastomas, TB, differential diagnosis, CD133, CD44, immunohistochemistry, receiver operating characteristic, ROC